Effect of vermicompost enriched with bacterial endophytes (Azospirillum and Rhizobium) on growth and yield of tomato - Nithya, S.; Sasikumar, K.; Raman, O. S. Sethu (Current Botany, 2024)
The extensive use of chemical fertilizers has served as a response to the increasing need for crop production in recent decades. While it addresses the demand for food, it has resulted in a decline in crop productivity and a heightened negative environmental impact. In contrast, bacterial endophytes namely Azospirillum and Rhizobium and vermicompost offer a promising alternative to mitigate the negative consequences of chemical fertilizers. It can enhance nutrient availability, promote plant growth, and improve nutrient uptake efficiency, thereby reducing the reliance on chemical fertilizers. In this study, two bacterial endophytes Azospirillum and Rhizobium, combination with vermicompost and chemical fertilizer were used to investigate their potential role in the enhancement of growth yields of tomato. The inoculation of bacterial endophytes enhanced the root and shoot length, biomass and leaf chlorophyll contents. The fruit weight of the tomato (kg/plant) was also higher in the vermicompost and bacteria inoculated plants of tomato than in the chemical fertilizer. The mixed application of vermicompost with the combination of Azospirillum and Rhizobium showed the best performance compared to other treatments.